Dementia: Not Only Alzheimer’s disease, an Eye on Frontotemporal Dementia - Galimberti, Daniela (2013)
This manuscript is an invited editorial to the review "Clinical, Genetic and Neuropathological Features of Frontotemporal Dementia: An Update and Guide" by Jorge Pelicano Paulos and João Massano.